Social Stress Increases Anxiety-Like Behavior Equally in Male and Female Zebrafish - Bozi, Brenno; Rodrigues, Jeane; Lima-Maximino, Monica; de Siqueira-Silva, Diógenes Henrique; Soares, Marta Candeias; Maximino, Caio (Frontiers in Behavioral Neuroscience, 2021)
Zebrafish anxiety-like behavior was assessed in the novel tank test after the formation of dominant-subordinate hierarchies. 10 pairs of animals were subjected to dyadic interactions for 5 days, and compared with control animals. After this period, a clear dominance hierarchy was established across all dyads, irrespective of sex. Social status affected parameters of anxiety-like behavior in the novel tank test, with subordinate males and females displaying more bottom-dwelling, absolute turn angle, and freezing than dominant animals and controls. The results suggest that subordinate male and female zebrafish show higher anxiety-like behavior, which together with previous literature suggests that subordination stress is conserved across vertebrates.